2014
DOI: 10.1590/01047760201420041422
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potassium application and soil moisture on the growth of Corymbia citriodora plants

Abstract: ABSTRACT:The objective of this work was to evaluate the effects of potassium and soil moisture levels on the growth of Corymbia citriodora plants. Four doses of potassium were applied (0, 40, 80 and 120 mg . dm -3 ) and three soil moisture levels were established (50-80%, 65-80% and 80% of maximum soil field capacity). The experiment was a 4 x 3 factorial arrangement of treatments within a randomized complete design with six replications for each treatment and one pot with two plants for each plot. At 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…In accordance with this, here the RWC, Ψ 1 and k leaf of cotton plants were significantly reduced by salt stress (Figure 7). Reports have indicated that higher shoot K + concentration and optimum K + /Na + ratio exert pivotal role in adjusting osmotic potential and turgor pressure of guard cells during stomatal movement, thus affecting transpiration rate and hydraulic conductance (Sa et al, 2014;Wang et al, 2013). In the present study, 150 mM NaCl salinity significantly decreased [K + ] leaf and [K + /Na + ] leaf of cotton plants (Figure 6b,c), indicating that salinity-induced decreased in RWC, Ψ 1 and k leaf could be associated with the reduction of [K + ] leaf and [K + / Na + ] leaf .…”
Section: The Relatively Less Reduction Ofmentioning
confidence: 99%
“…In accordance with this, here the RWC, Ψ 1 and k leaf of cotton plants were significantly reduced by salt stress (Figure 7). Reports have indicated that higher shoot K + concentration and optimum K + /Na + ratio exert pivotal role in adjusting osmotic potential and turgor pressure of guard cells during stomatal movement, thus affecting transpiration rate and hydraulic conductance (Sa et al, 2014;Wang et al, 2013). In the present study, 150 mM NaCl salinity significantly decreased [K + ] leaf and [K + /Na + ] leaf of cotton plants (Figure 6b,c), indicating that salinity-induced decreased in RWC, Ψ 1 and k leaf could be associated with the reduction of [K + ] leaf and [K + / Na + ] leaf .…”
Section: The Relatively Less Reduction Ofmentioning
confidence: 99%
“…The relative water content of custard apple plants also increased linearly in response to potassium fertilization, and according to the regression equation (Figure 1B), there was an increase of 2.196% for each 5 g increment in K 2 O dose. Plants subjected to fertilization with a higher potassium dose (30 g per plant) increased their RWC by 10.74% compared to those receiving the K 2 O dose of 10 g. Potassium supply contributed to osmotic adjustment in plants under low water availability because excess salt in water reduces the water potential (A. F. L. de Sá et al, 2014). Osmotic adjustment is an important characteristic associated with the maintenance of high cell turgor potential and water retention in response to salt stress, being fundamental for the survival of plants under salt stress conditions, highlighting the role of K + in the regulation of turgor within the guard cells during stomatal movement (Wang, Zheng, & Guo, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…At the end of the exposure period, plant growth was assessed on all plants by measuring plant height, stem diameter (near the base) and total number of leaves. For measurements of height and stem diameter, a measuring tape and a digital caliper (data expressed in cm) (Digimess, São Paulo, Brazil) were used (Sá et al, 2014), respectively.…”
Section: Growth and Biomassmentioning
confidence: 99%